Sporothrix schenckii Immunization, but Not Infection, Induces Protective Th17 Responses Mediated by Circulating Memory CD4+ T Cells - García-Lozano, Alberto; Toriello, Conchita; Antonio-Herrera, Laura; Bonifaz, Laura C. (Frontiers in Microbiology, 2018)
Sporotrichosis is a chronic subcutaneous mycosis caused by the Sporothrix schenckii species complex and it is considered an emerging opportunistic infection in countries with tropical and subtropical climates. The host’s immune response has a main role in the development of this disease. However, it is unknown the features of the memory cellular immune response that could protect against the infection. Our results show that i.d. immunization in the ears of mice with inactivated S. schenckii conidia (iC) combined with the cholera toxin (CT) induces a cellular immune response mediated by circulating memory CD4+ T cells, which mainly produce interleukin 17 (IL-17). These cells mediate a strong delayed-type hypersensitivity (DTH) reaction. Systemic and local protection against S. schenckii was mediated by circulating CD4+ T cells. In contrast, the infection induces a potent immune response in the skin mediated by CD4+ T cells, which have an effector phenotype that preferentially produce interferon gamma (IFN-γ) and mediate a transitory DTH reaction. Our findings prove the potential value of the CT as a potent skin adjuvant when combined with fungal antigens, and they also have important implications for our better understanding of the differences between the memory immune response induced by the skin immunization and those induced by the infection; this knowledge enhances our understanding of how a protective immune response against a S. schenckii infection is developed.